2017
DOI: 10.1371/journal.pone.0182868
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants of emerging concern in tributaries to the Laurentian Great Lakes: I. Patterns of occurrence

Abstract: Human activities introduce a variety of chemicals to the Laurentian Great Lakes including pesticides, pharmaceuticals, flame retardants, plasticizers, and solvents (collectively referred to as contaminants of emerging concern or CECs) potentially threatening the vitality of these valuable ecosystems. We conducted a basin-wide study to identify the presence of CECs and other chemicals of interest in 12 U.S. tributaries to the Laurentian Great Lakes during 2013 and 2014. A total of 292 surface-water and 80 sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 47 publications
4
62
1
Order By: Relevance
“…As EEQ of E 1 , NP and BPA were 0.8, 0.0036 and 0.0026 at their maximum as compared with E 2 as 1 (Schultz et al, ), 1× AG and 1× UB mixtures have the potential to activate Esr at 37.9% and 57.8% when compared with E 2 . At the highest level, the 10× UB mixture via fathead minnow Esr1 showed 10 –10.17 m (0.068 n m ) EEQ, which differed to what has been documented in Great Lake tributaries as per Elliott et al (). Kortenkamp () summarized that effects of a low‐dose mixture of endocrine disruptors would fit a concept of concentration addition rather than an independent action.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…As EEQ of E 1 , NP and BPA were 0.8, 0.0036 and 0.0026 at their maximum as compared with E 2 as 1 (Schultz et al, ), 1× AG and 1× UB mixtures have the potential to activate Esr at 37.9% and 57.8% when compared with E 2 . At the highest level, the 10× UB mixture via fathead minnow Esr1 showed 10 –10.17 m (0.068 n m ) EEQ, which differed to what has been documented in Great Lake tributaries as per Elliott et al (). Kortenkamp () summarized that effects of a low‐dose mixture of endocrine disruptors would fit a concept of concentration addition rather than an independent action.…”
Section: Discussioncontrasting
confidence: 60%
“…The highest estimated EEQ of water in Great Lake tributaries was 25 ng l –1 (0.092 n m = 10 –10.04 m ) based on fathead minnow vitellogenin productions (Elliott et al, ), and AC 50 of E 2 via human Esr1 was 0.10 n m according to the US EPA Tox21 ToxCast Dashboard (https://actor.epa.gov/dashboard) (Dix et al, ). As EEQ of E 1 , NP and BPA were 0.8, 0.0036 and 0.0026 at their maximum as compared with E 2 as 1 (Schultz et al, ), 1× AG and 1× UB mixtures have the potential to activate Esr at 37.9% and 57.8% when compared with E 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It was expected that agricultural land use would be associated with the presence of pesticides, herbicides (Elliott et al 2017;Nowell et al 2018), and livestock-specific chemicals (i.e., growth promoters, steroids, livestock pharmaceuticals; Jaffrézic et al 2017). Biological effects from agricultural CECs include feminized sex ratios (Hoskins and Boone 2017), reductions in fecundity (Jensen et al 2006), and a reduction in species abundance and total number (Schäfer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some insights into chemical co‐occurrence can be gained by multivariate statistical methods, such as cluster analyses. Previous multivariate analyses have shown that some chemicals tend to co‐occur at sites with similar land use across the Great Lakes Basin (Elliott et al ). For example, atrazine, metolachlor, and flame retardants tend to co‐occur at sites with a dominant agricultural land use.…”
Section: Introductionmentioning
confidence: 99%